Guiding the Eye - Vermeersch, Lode,Wagner, Ernst,Wenrich, Rainer (Waxmann, 2019)
This book addresses the link between visual literacy – people’s ability to interpret and skillfully use images – and art museums. Art museums invite you to look at objects in different ways. They stimulate your visual curiosity, give you visual satisfaction, and allow the visual to merge with other sensory experiences. All of this makes art museums potentially the ideal learning environments for acquiring visual literacy skills. But how should an art museum stimulate visual literacy in practice? How can it actually become such an ideal learning place? How can it spark visitors’ visual literacy and increase their knowledge about it? In this book a wide range of authors from different parts of the world offer their answers. As researchers, curators and educators they provide crucial theoretical insights and reflect on real-life examples.
9783830991120
Keywords: Aufsatzsammlung; Art Mediation; Art Museum Education Outreach; Art Museums; Automotive Design; Cultural Education; Curator; Design Museums; Erwachsenenbildung; Fashion; Kyoto International Manga Museum; Ludwig Forum for International Art Aachen; Manga; Museum of Decorative Arts Prague; Pinakothek der Moderne; Schulpädagogik; State Textile and Industry Museum Augsburg; The Digitorial®; The National Gallery of Victoria; The RETINA Project; Visual Competence; Visual Literacy; Schools; Pupils